Jonas Basanavičius and Sigmund Freud, or How “the Patriarch of the Revival” Fought Nerve Diseases - Raila, Eligijus (Lietuvos istorijos studijos, 2017)
This article is a micro-historic research dealing with a particular fragment of Jonas Basanavičius’ life. It is related to the “history of the nervous disease” of doctor Jonas Basanavičius. We discovered that the surname of neurologist Sigmund Freud is mentioned in the doctor’s notebooks from years 1894 and 1895. The article poses a hypothesis that Jonas Basanavičius, while in search of the causes of his physical ailments, might have sought consultation with Sigmund Freud. Basanavičius was in contact with people from Freud’s circle. Moreover, Freud’s treatise Die Traumdeutung has most certainly influenced Basanavičius’ auto-biographical narration.
Keywords: Jonas Basanavičius; Sigmund Freud; psychoanalysis; nervous disease